Effect of Red Dragon Fruit Extract as Dye in Solar Cells - Eliyana, Ajeng; Puspitarum, Deska Lismawenning; Laksono, Dana (Jurnal ILMU DASAR, 2020)
Along with the development of nanotechnology, the development of solar cells entered a significant stage with the emergence of the newest generation, namely DSSC (Dye Sensitized Solar Cell). The utilization of dragon fruit skin which has been extracted as dye in dye sensitized solar cells and solar cell development to realize sustainable energy supply is the main target in this study. The method carried out begins with the synthesis of nanoparticles from organic material (TiO2), to obtain good TiO2 material as an anti-reflection, where anti-reflection is selected on DSSC technology to reduce light reflection in the visible light region. The crystal size of TiO2 was analyzed as an oxide layer material in DSSC. DSSC synthesis was carried out and the parameters of organic solar cell devices (DSSC) were optimized to obtain solar cells with good conversion efficiency. The results showed that the size of TiO2 obtained was an average of 0.211 nm and the maximum wavelength value of the extract of the dragon fruit dye solution was 530 nm. Keywords: dye, solar cell, DSSC, TiO2.